2020
DOI: 10.1155/2020/1935742
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Red Blood Cell Distribution Width in Chronic Obstructive Pulmonary Disease Patients with Pulmonary Embolism

Abstract: Purpose. This study is aimed at investigating the relationship between red cell distribution width (RDW) and chronic obstructive pulmonary disease (COPD) patients with pulmonary embolism (PE). Methods. We conducted a retrospective study enrolling a total of 125 patients from January 2013 to December 2019. The study group consisted of 40 COPD patients with PE, and the control group had 85 COPD patients without PE. Clinical data including demographic characteristics, comorbidities, and results of imaging examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…Consistent with previous systematic reviews [ 6 , 15 ], our study revealed that the incidence of DVT among AE-COPD was lower than that of PE. Five studies were excluded from our original analyses because they enrolled patients with COPD and not those with AE-COPD [ 38 42 ]. Including these five studies in the analysis yields a slight increase in PE prevalence in COPD patients (19.9%; 95% CI, 15.2%-25.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with previous systematic reviews [ 6 , 15 ], our study revealed that the incidence of DVT among AE-COPD was lower than that of PE. Five studies were excluded from our original analyses because they enrolled patients with COPD and not those with AE-COPD [ 38 42 ]. Including these five studies in the analysis yields a slight increase in PE prevalence in COPD patients (19.9%; 95% CI, 15.2%-25.7%).…”
Section: Discussionmentioning
confidence: 99%
“…PE and AE-COPD are very similar, and the two are often indistinguishable clinically. Therefore, PE is easily neglected in patients with AE-COPD, resulting in delayed treatment and poor prognosis [ 14 , 38 ]. Our study suggests that these clinical symptoms merit clinical attention and should be taken into account in patients with unexplained AE-COPD after excluding respiratory tract infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 Subsequently, Kalemci confirmed the previously reported results. 24 The RDW can also be used to predict high risk for COPD complicated with pulmonary hypertension, 25 pulmonary embolism, 26 and pulmonary heart disease. 27 A study of 307 patients concluded that the RDW also has clinical diagnostic value for depression and/or anxiety associated with AECOPD, and may become a new indicator of inflammation in AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“… 2 A population-based retrospective cohort study found that 12.31 out of 10,000 COPD patients developed PE each year, approximately four times the rate of non-COPD patients. 3 In addition, the prevalence of PE has been noted to be higher among acute exacerbations of chronic obstructive pulmonary disease (AECOPD) patients. 4 Venous thromboembolism (VTE) is a type of disease including deep vein thrombosis (DVT) and PTE.…”
Section: Epidemiologymentioning
confidence: 99%